A pilot, quasi-experimental, mixed methods investigation into the efficacy of a group psychotherapy intervention for caregivers of outpatients with cancer: the COPE study protocol. Issue 11 (19th November 2015) - Mahendran, Rathi; Tan, Joyce Yi Siang; Griva, Konstadina; Lim, Haikel Asyraf; Ng, Hui Ying; Chua, Joanne; Lim, Siew Eng; Kua, Ee Heok
Abstract : Introduction: Despite the rising trend of cancer prevalence and increase in family caregiving, little attention has been paid to the efficacy of psychosocial interventions among Asian caregiver samples, particularly support groups, given the benefits that have been shown in studies on Western populations. This trial aims to evaluate the effectiveness of a pilot 4-week group psychotherapy for Singaporean family caregivers of patients receiving outpatient care. Methods and analysis: Facilitated by a clinical psychologist, this intervention is primarily based on the brief integrative psychological therapy with a supportive-expressive intent. Participants will be recruited while they are accompanying their care recipients for outpatient consultations. Since this is a pilot study, a sample size of 120 participants is targeted on the basis of sample sizes of previous studies. The study adopts a quasi-experimental design, as participants are assigned the intervention or control arms based on their availability to attend the intervention. A mixed methods approach is used to evaluate the outcomes of the intervention. A self-administered battery of tests is completed at four time points: baseline, postintervention and follow-up at 1-month and 2-month postinterventions; semi-structured interviews are conducted at baseline and post-intervention. Primary outcomes are quality of life and anxious and depressive symptoms; secondary outcomes are stress and basic psychological needs. Analysis using analysis of covariance would be conducted to determine the effectiveness of the intervention. Ethics and dissemination: This study protocol has ethics approval from the National Healthcare Group Domain Specific Review Board (NHG DSRB Ref: 2013/00662). Written informed consent is obtained from every participant. Results will be disseminated through journals and conferences, and will be particularly relevant for clinicians intending to implement similar support groups to address the psychosocial concerns of caregivers, as well as for researchers seeking to refine the structure and evaluate the effectiveness of such programmes. Trial registration number: Current Controlled Trials NCT02120183 (https://clinicaltrials.gov/show/NCT02120183 )